The Effect of plickers implementation on 6th Grade Students’ locus of control (LoC) and misconceptions - MERTOĞLU, HATİCE (My University, 2023)
The purpose of this survey is to define the effect of Plickers implementation applied in science lessons on students’ locus of control (LoC) and misconceptions. The experimental design was determined as the single-group pre-test and post-test. Fifty-one students studying in the 6th grade participated in the survey. The Nowicki-Strickland Locus of Control Scale (LoC) for Children and the word association test (WAT) is utilized to identify misconceptions at the beginning and end of the lesson. As a result, it was observed that some of the misconceptions of the students changed after the Plickers implementation, but some of the misconceptions did not change. However, after Plickers, it was defined that the LoC points of girls decreased, and the points of boys increased. When the students were examined in general, it was defined that the post-test points they got from the scale were lower than the pre-test points. Although this result does not show any distinction, it is an indication that students’ LoC levels are visibly inclined towards inner LoC. In the results of the survey, it can be suggested that the Plickers implementation be used actively in eliminating students’ misconceptions and developing their LoC.
Keywords: Word association test (WAT); Plickers; Locus of control; Misconceptions